2019
DOI: 10.1158/0008-5472.can-19-0037
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish MITF-Low Melanoma Subtype Models Reveal Transcriptional Subclusters and MITF-Independent Residual Disease

Abstract: Zebrafish MITF-low melanoma models human MITF-low melanoma. While the bulk of the tumor is dependent on MITF activity, MITF-independent cells preexist and arise de novo in residual disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(102 citation statements)
references
References 54 publications
9
86
0
Order By: Relevance
“…Among the genes that overlap between the MRD and ∆MITF-X6 cells are ECM genes such as COL4A1, ITGA1, ITGA6, LAMC1 and VCAN. The same findings were obtained using single cell RNA-Seq data of MITF-depleted zebrafish melanomas as well as bulk-RNA-Seq data of MITFlow melanoma tumours [22]. Both datasets showed positive enrichment with ∆MITF-X6 cells ( Supplementary Fig.…”
Section: Mitf Affects the Number Of Focal Adhesionssupporting
confidence: 77%
See 2 more Smart Citations
“…Among the genes that overlap between the MRD and ∆MITF-X6 cells are ECM genes such as COL4A1, ITGA1, ITGA6, LAMC1 and VCAN. The same findings were obtained using single cell RNA-Seq data of MITF-depleted zebrafish melanomas as well as bulk-RNA-Seq data of MITFlow melanoma tumours [22]. Both datasets showed positive enrichment with ∆MITF-X6 cells ( Supplementary Fig.…”
Section: Mitf Affects the Number Of Focal Adhesionssupporting
confidence: 77%
“…Immunohistochemistry and single-cell sequencing studies of melanoma tumours have shown the existence of cells with low or no MITF expression [20][21][22]. The involvement of MITF in migration has mostly been characterized using knockdown studies in melanoma cell lines using either siRNA or shRNA and by using Matrigel-coated Boyden chambers [14,[44][45][46]; in these studies knocking down MITF resulted in increased migration properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) Melanoma modifiers introduced into the Tg(mitfa:BRAF V600E ); p53(lf) model using MiniCoopR (MCR) resulted in aggressive melanomas, comparable to other models with alternative tumor drivers such as NRAS proto-oncogene, GTPase (NRAS Q61K ) or HRas proto-oncogene, GTPase (HRAS G12V ) [21,27,36,[45][46][47][48]. (E) Expression of HEXIM P-TEFb complex subunit 1 (HEXIM1) using MiniCoopR, or loss of growth differentiation factor 6 alpha (gdf6a) in a Tg(mitfa:BRAF V600E );p53(lf) background led to delayed melanoma onset [36,49].…”
Section: Using Zebrafish To Discover Genetic Modifiers Of Melanomamentioning
confidence: 88%
“…Previous scRNA-Seq melanoma studies have revealed multiple cell states in melanoma, including neural crest, pigmented, invasive and starved states (Rambow et al, 2018) . We and others have previously shown that the neural crest transcriptional program, typified by genes such as SOX10 , is essential to melanoma initiation because it provides the proper mileu on which DNA mutations can act (Kaufman et al, 2016;Shakhova et al, 2012;Travnickova et al, 2019;White et al, 2011) . In contrast, the existence of other cell states such as a "stress-like" state, expressing genes such as fos and jun , has been suggested by prior work but its functional role remains unclear (Tirosh et al, 2016a) .…”
Section: Introductionmentioning
confidence: 99%